MODEL KNOWLEDGE MANAGEMENT SYSTEM PADA PERGURUAN TINGGI DENGAN STRUCTURAL EQUATION MODELLING (SEM) - Ni Luh Ayu Kartika Yuniastari Sarja (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTknowledge management system(KMS) is an information system that support knowledge management activities in universities . KMS isvery necessary to facilitate acces and utilization order for implenentationmodelcan be made in the form of a model. build KMS model can be made in the form of a model. build KMS model can be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS model can be made in the form of a model. build KMS model can be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS model can be made in the form of a model. build KMS model can be made in the form of a model. build KMS model can be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS model can be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS model can be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS model can be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS model can be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS model can be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS model can be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS model can be made in the form of a model. build KMS modelcan be made in the form of a model. build KMS model and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. and test the model that has been built. This This This knowledge management system knowledge management systemknowledge management systemknowledge management system knowledge management systemknowledge management system knowledge management system knowledge management systemknowledge management systemknowledge management systemknowledge management system knowledge management systemknowledge management system knowledge management systemknowledge management system model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding model was built to provide a more complete understanding of the utilization of the utilization of the utilization of the utilization of the utilization of the utilization of the utilization of the utilization of the utilization of the utilization of the utilization of the utilization of the utilization knowledge management system knowledge management systemknowledge management systemknowledge management system knowledge management systemknowledge management system knowledge management system knowledge management systemknowledge management systemknowledge management systemknowledge management system knowledge management systemknowledge management system knowledge management systemknowledge management system s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the s in higher education. To find out the compatibility in the implementation o compatibility in the implementation o compatibility in the implementation ocompatibility in the implementation o compatibility in the implementation o compatibility in the implementation o compatibility in the implementation o compatibility in the implementation ocompatibility in the implementation o compatibility in the implementation o compatibility in the implementation o compatibility in the implementation o compatibility in the implementation ocompatibility in the implementation o compatibility in the implementation o compatibility in the implementation ocompatibility in the implementation ocompatibility in the implementation of the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of f the model with real environment, a test of was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental was carried out. Testing is done so that the model in accordance with environmental conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research conditions. Testing is done using the Structural Equation Modeling (SEM) model. The research method used refer method used refermethod used refermethod used refermethod used refermethod used refermethod used refer method used refermethod used refermethod used refer s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can s to the information system research framework. The results of this study can be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely be concluded that the KMS model in higher education consists of three constructs, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely regulation, KMS and strategy. In the construct, there are construct elements, namely process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory process, people and software. The results of the model evaluation show that regulatory constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS. constructs and strategies have a significant influence on KMS.